GRP-043 Concurrent Use of Different Benzodiazepines in Different Healthcare Levels. (12th March 2013) - Sotoca, J; Rovira, M; Codina, C; Ribas, J
Abstract : Background: Benzodiazepines are the most commonly-used anxiolytics and hypnotics. Concern has been expressed regarding their potential over-prescription. Different benzodiazepines have fundamentally the same mechanism of action and differ from each other mainly by differences in pharmacokinetics. There is no pharmacological basis for using more than one benzodiazepine in the same patient. Purpose: The purpose of this study was to study the prevalence of concurrent use of different benzodiazepines in different healthcare levels in the same area: primary care, tertiary level hospital discharge and ambulatory mental health centre. Materials and Methods: Data were obtained from the pharmacy claims database between 1st and 31st January 2012. Patients who had been dispensed at least one benzodiazepine during January 2012 were included (n = 1707 in primary care, n = 273 at tertiary level hospital discharge and n = 128 in an ambulatory mental health centre). The proportion of benzodiazepine users was calculated and broken down by gender and age. Results: The number of patients who were dispensed two or more different benzodiazepines simultaneously was 124 (7.3%) in primary care, 11 (4.0%) in hospital discharge and 1 (0.8%) in the ambulatory mental health centre. Most patients who were prescribed benzodiazepines were women (between 60% and 70% depending on the health care setting). Women benzodiazepines users were younger in the ambulatory mental health centre (mean age 51 years) than at hospital discharge (mean age 64 years) or in primary care (mean age 68 years). Conclusions: There was more detrimental prescribing of different benzodiazepines simultaneously in primary care than at hospital discharge or in an ambulatory mental health centre. In patients who used benzodiazepines simultaneously, they were mainly prescribed by the same physician. No conflict of interest.